Asymptotic expansion of a semi-Markov random evolution - Samoilenko, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We determine the regular and singular components of the asymptotic expansion of a semi-Markov random evolution and show the regularity of boundary conditions. In addition, we propose an algorithm for finding initial conditions for t = 0 in explicit form using the boundary conditions for the singular component of the expansion.